Implementasi Pola Asuh Demokratis Dalam Mendorong Kemandirian Anak Usia 4-5 Tahun (Tk Darul-Arqom Di Desa TanjungAnom Kecamatan Samarang Kabupaten Garut) - Aliyah, Siti; Susiani, Desi (LP2M STAI Al-Musaddadiyah Garut, 2022)
Parents always hope that their children can develop perfectly. They want their children to grow up to be morally excellent, independent, strong, personality-rich, creative, intelligent, and obedient to their religious teachings. To achieve this desire, parents have a primary role because they are the primary educators (Al ummah madrhosatul ula) and serve as role models for their children before they are exposed to education outside the family. Relevant parenting styles can stimulate children's independence development. Lake Crouter & McHale state that independence is recognized as a crucial aspect of developmental education. Independence does not develop on its own but requires a continuous process, indicating that independence needs to be instilled from an early age. Considering that independence is essential in life, as long as parents are willing to change their parenting methods for the development of their children. A democratic parenting style is highly relevant in promoting independence in 4-5-year-old children. The independent behavior of children is produced because parents implement a democratic parenting style that involves two-way communication. The implementation of a democratic parenting style greatly assists in fostering the independence of 4-5-year-old children at Tk Darul-Arqom in Tanjung Anom Village, Samarang District. Democratic parents show full expression of love and responsiveness to their children, allowing them freedom with responsibility under careful supervision. This study aims to determine the level of independence in 4-5-year-old children, understand the form of democratic parenting styles in promoting independence in 4-5-year-old children, and understand the implementation of democratic parenting styles in fostering independence in 4-5-year-old children. Keywords: Implementation of Democratic Parenting Styles, Independence of 4-5-Year-Old Children